Caught in-between : intermediality in contemporary Eastern European and Russian cinema - Pethő, Ágnes (Edinburgh studies in film and intermediality., 2020)
"This collection of essays explores intermediality as a new perspective in the interpretation of the cinemas that have emerged after the collapse of the former Eastern bloc. As an aesthetic based on a productive interaction of media and highlighting cinema's relationship with the other arts, intermediality always implies a state of in-betweenness which is capable of registering tensions and ambivalences that go beyond the realm of media. The comparative analyses of films from Hungary, Romania, Poland, the Czech Republic, Bosnia and Herzegovina and Russia demonstrate that intermediality can be employed in this way as a form of introspection dealing with complex issues of art and society. Appearing in a variety of sensuous or intellectual modes, intermediality can become an effective poetic strategy to communicate how the cultures of the region are caught in-between East and West, past and present, emotional turmoil and more detached self-awareness. The diverse theoretical approaches that unravel this in-betweenness contribute to the understanding of intermedial phenomena in contemporary cinema as a whole."--Publisher description